PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VII A DALAM MATA PELAJARAN IPS DI SMPN 4 MANDAU - Dame Uli Lumban Tobing; Isjoni '; Bedriati Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstack: The Problem Based Learning model is a learning model that presents students with authentic and meaningfull problems so as to make it easier for them to conduct an investigation and inquiry. Problem Based Learning aims to assist student in developing thinking skill to problem solving and intellectual skills. In addition to training the knowledge and skills of students, this model is also expected to improve student learning outcomes. In this research aims to improve the learning outcomes of students social studies classes VII in SMPN 4 Mandau with problem based learning model. The location of this research in SMPN 4 Mandau district Mandau district Bengkalis. Samples in this study is a Class VII A SMPN 4 Mandau amounting to 36 people. Data were obtained by a test sheet student learning outcomes. Data analysis techniques performed by observation of the teacher's behavior and collect data to learn the results obtained from the social studies test students and analyzed with descriptive statistical techniques. From the analysis result that after the implementation of problem based learning model, there is increased activity of teachers, increase the activity of students and student learning outcomes also increased. From the results of research conducted suggested that primary school teachers in SMPN 4 Mandau can use problem based learning as an alternative learning to improve student learning outcomes.Keywords: Problem Based Learning model, Learning Outcomes